The Transfer of Japanese Manufacturing Management Approaches to U.S. Industry - Schonberger, Richard J. (Academy of Management Review, 1982)
Just-in-time (JIT) provisioning of manufacturing inventories is a notable feature of Japanese manufacturing management. Kawasaki Motors, USA, has committed itself to JIT objectives, which result in moving toward lotless repetitive manufacturing, a streamlined mode of operation characterized by minimal inventories and “shop paper,” plus flexible market response. Kawasaki USA has forged a hybrid process of effecting change, featuring Japanese JIT objectives but without Japanese-style consensus mechanisms for making decisions and effecting changes.